2002
DOI: 10.1046/j.1365-3180.2002.00264.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of tillage, cover crop and crop rotation on the composition of weed flora in a sandy soil

Abstract: The development of integrated weed management strategies requires knowledge of mechanisms that influence compositional changes in weed flora. A 9‐year study was initiated in 1988 at Delhi, Canada, on a loamy sand soil to evaluate the effect of tillage systems [conventional (CT) and no‐till (NT)] and cover crops (only in NT) on weed density, species composition and associations, and crop yield in a winter wheat (Triticum aestivum L.)/bean/winter wheat rotation. Three bean types: soyabean (Glycine max L. Merr.),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
90
0
6

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 127 publications
(102 citation statements)
references
References 49 publications
6
90
0
6
Order By: Relevance
“…The weeds were cut even with the ground in two randomly sorted areas delimited by a 0.5 × 0.5 m wooden frame in the net plot subplot. Weed species relative frequency (Shrestha et al, 2002) was calculated based on the information obtained from each subplot (in both 0.5 × 0.5 m areas sampled from each subplot, as previously mentioned) and was defined as the ratio between number of plots where each species occurred and total number of plots (60) in the experiment.…”
Section: Methodsmentioning
confidence: 99%
“…The weeds were cut even with the ground in two randomly sorted areas delimited by a 0.5 × 0.5 m wooden frame in the net plot subplot. Weed species relative frequency (Shrestha et al, 2002) was calculated based on the information obtained from each subplot (in both 0.5 × 0.5 m areas sampled from each subplot, as previously mentioned) and was defined as the ratio between number of plots where each species occurred and total number of plots (60) in the experiment.…”
Section: Methodsmentioning
confidence: 99%
“…Facelli and Pickett (1991), as well as Shrestha et al (2002), observed that the type of plant residue cover affected the weed species composition. Consequently, there is a need for future studies to document the response of the weed flora to different cover crops and their mulches (Dastgheib & Frampton, 2000).…”
Section: Introductionmentioning
confidence: 94%
“…Treatment the cover crops (end of May) terminated the dominance of ryegrass in most of these treatments ( Swanton et al, (1999), Shrestha et al (2002) and Westra et al (2008). Stinging milkweed disappeared from all the cover crop treatments, with the exception of Nemat (MC).…”
Section: Tablementioning
confidence: 99%
See 1 more Smart Citation
“…in glyphosate-resistant cotton CT systems. Shrestha et al (2002) concluded that long-term changes in weed flora are driven by an interaction of several factors: tillage, environment, crop rotation, crop type, and the timing and type of weed management practice.…”
Section: T Illage An D Wee D Managementmentioning
confidence: 99%